(3GdYed GdeUQaj GdGdcJQhfj aj GdHdOGf GdYQHjI (B/s - (3SaQ, GMeOs ((3WQGHdS(B: s (3GdeDSSSI GdMOjKI ddcJGH(B, s, 2006)
(3jJWQb GdcJGH ddehGVjY GdJGdjI (B: (3GdHjFI GdeUQajI h GdJcfhdhLjI, QcGFR GdYed GdeUQaj GdGdcJQhfj, HfjI GdGYeGd GdeUQajI GdGdcJQhfjI h JMOjGJgG, NOeGJ GdUjQaI GdGddcJQhfjI h LQGFegG, GdHfhc GdEdcJQhfjI, JbfjI GdeYdheGJ h GSJNOGeGJ GdUjQaI h GdfbhO GdGdcJQhfjI, ebheGJ GdJhbjY GdGdcJQhfj, GdGWGQ GdbGfhfj ddYed GdeUQaj h CNjQG GdJLQHI GddHfGfjI aj GdUjQaI GdGdcJQhfjI(B. s
Keywords: (3GdHfhc(B-(3egfIs; (3GdYGde GdYQHj (B-(3GdCMhGd GdGbJUGOjI s; (3JcfhdhLjGs